2015
DOI: 10.1007/s00383-015-3808-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vasculogenic potential of human adipose-derived endothelial cells in a three-dimensional vascularized skin substitute

Abstract: Adipose tissue represents an attractive cell source due to the ease of isolation and abundance of endothelial as well as mesenchymal cell lineages. Adipose-derived SVF cells exhibit the ability to form microvascular structures in vitro and support the accelerated blood perfusion in skin substitutes in vivo when transplanted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
72
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 40 publications
12
72
0
3
Order By: Relevance
“…showed that the endothelial part of SVF exhibited the ability to form microvascular structures in vitro and support the accelerated blood perfusion in skin substitutes in vivo . 9 This study confirmed their previous experiments and also the study conducted by Atalay et al . in 2014.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…showed that the endothelial part of SVF exhibited the ability to form microvascular structures in vitro and support the accelerated blood perfusion in skin substitutes in vivo . 9 This study confirmed their previous experiments and also the study conducted by Atalay et al . in 2014.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies in the aesthetic field for skin rejuvenation 6 confirm that ADSCs increase the dermal collagen synthesis and even vascularity via production of many cytokines and growth factors. 7-9 It has been shown that ADSCs secrete growth factors that have an effect on fibroblast and keratinocyte proliferation. 10-12 Some researchers reported that the ADSCs could be differentiated into epithelial lineage and make their effect on the aged or damaged skin.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to assess the efficacy of fat grafting on facial rejuvenation [1, 15-17], with the results suggesting that such rejuvenation effects result from the improvement of deep facial structures. In contrast, others have suggested that ASCs, which are abundant in fat tissue, participate in soft tissue remodeling by promoting collagen synthesis, cellular matrix protein synthesis, and revascularization of the dermis via the production of many cytokines and multipotential proliferation [17-20]. …”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic digestion of fat tissue allowed for the production and separation of tissue components via centrifugation, ultimately providing the ability to isolate buoyant adipocytes and dense cellular pellets, the latter of which would be described as stromal vascular fraction. Within this dense cellular pellet there are a multitude of cell types including endothelial cells, smooth muscle cells, fibroblasts, pericytes, perivascular cells, immune cells, adipose stem cells, and mesenchymal stem cells [84][85][86][87][88] .…”
Section: The Stromal Vascular Fractionmentioning
confidence: 99%
“…systems that can provide a stimulating microenvironment for embedded cells in order to mature into tissue units 88,214 . Most 3D systems utilize a mixture of cells with a scaffold or substrate that provides sites for cell adhesion and migration, as well as threedimensionality, more closely mimicking endogenous tissue histological layouts.…”
Section: Am Live Stain At Day 2 (B) and Day 6 (F) Ethidium Homodimermentioning
confidence: 99%